Inter- and transdisciplinary collaboration in an international research project: The case of the German-Ghanaian project EnerSHelF (Energy-Self-Sufficiency for Health Facilities in Ghana) - Jonas Bauhof; Katja Bender; Stefanie Meilinger; Sarah Rabe (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2024)
Interdisciplinary research (IDR) is a widely applied research approach, combing the efforts of multiple academic disciplines to work on complex problems. Within transdisciplinary research (TDR), non-academic stakeholders participate in the project and offer hands-on experience to the research. These integrative approaches are praised for the ability for addressing 'wicked problems' and can lead to new perspectives on relevant contemporary challenges. This working paper is analysing the cooperation and exchange of involved disciplines in the German-Ghanaian interdisciplinary research project Energy-Self-Sufficiency for Health Facilities in Ghana (EnerSHelF). The results are presented in a Collaboration Frequency Network (CFN) as well as qualitatively examined to unravel the level of interaction and perspectives on chances and challenges of IDR and TDR. The analysis shows that disciplinary closeness, data collection and exchange, and individual effort are affecting the level of collaboration among other reasons. Concluding the authors develop recommendations for future IDR and TDR projects.
urn:nbn:de:hbz:1044-opus-83694
Keywords: 650; Forschungskooperation; Interdisziplinäre Forschung; Projektbewertung; Energieeinsparung; Gesundheitswesen; Deutschland; Ghana